2018
DOI: 10.1590/s2179-975x10616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of invasive species snails in continental aquatic bodies of Pernambucano semiarid

Abstract: Aim: The aim of this study was to survey the species of molluscs and to evaluate the effect of exotic species on the native mollusks of three reservoirs in the Pajeú Basin Cachoeira II, Jazigo and Serrinha. Methods: Sampling was carried out with trawl net (5 mm mesh opening) and hand net (2 mm mesh opening). Results and conclusions: Were quantified 60,244 specimens, distributed among the species Melanoides tuberculata (49,398), Pomacea lineata (573), Biomphalaria straminea (376) and Physa marmorata (01). The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…The high number of individuals observed is a consequence of the set of biological traits mentioned, which allows M. tuberculata to become a successful competitor in new environments, capable of even suppressing the growth of native species population. The role of this invasive species in the reduction of native species have been described in different environments (Freitas et al 1987, Pointier 1999, Fernandez 2001, Almeida et al 2018). There are reports of the decline in B. glabrata and B. straminea densities from the Southeastern region (Giovanelli et al 2003, Almeida et al 2018, as well as it was responsible for the low diversity and density indices of native species in Northeastern reservoirs (Almeida et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high number of individuals observed is a consequence of the set of biological traits mentioned, which allows M. tuberculata to become a successful competitor in new environments, capable of even suppressing the growth of native species population. The role of this invasive species in the reduction of native species have been described in different environments (Freitas et al 1987, Pointier 1999, Fernandez 2001, Almeida et al 2018). There are reports of the decline in B. glabrata and B. straminea densities from the Southeastern region (Giovanelli et al 2003, Almeida et al 2018, as well as it was responsible for the low diversity and density indices of native species in Northeastern reservoirs (Almeida et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The role of this invasive species in the reduction of native species have been described in different environments (Freitas et al 1987, Pointier 1999, Fernandez 2001, Almeida et al 2018). There are reports of the decline in B. glabrata and B. straminea densities from the Southeastern region (Giovanelli et al 2003, Almeida et al 2018, as well as it was responsible for the low diversity and density indices of native species in Northeastern reservoirs (Almeida et al 2018). Although the effect of M. tuberculata on mollusk community of the São Julião reservoirs has not been evaluated, the expressive differences observed among abundances of this species, B. straminea and Pomacea lineata, suggest attention to a putative interspecific competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot be ruled out that invasive species such as Melanoides tuberculata are at least partly responsible for the loss of gastropod diversity in the Laguna District. This species has long been suspected of displacing native populations (Thompson, 2004;Almeida et al, 2018). Although extirpation and invasion coincide temporally and spatially in the area of study, a causal relationship such as interspecific competition or increased parasitism is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This set of biological features allow for M. tuberculata to out-compete with other species in newly invaded places mainly due to its capacity to suppress populations of native species. Its presence in reservoirs in semiarid Brazil is said to be responsible for the low diversity of native mollusks in these areas (Almeida et al 2018). Fernandez et al (2001 reported on the decline of a population of Pomacea lineata (Spix, 1827) due to the presence of M. tuberculata.…”
Section: Discussionmentioning
confidence: 99%